Intravesical electrical stimulation of the bladder – animal model study in HUSM - AH, Azhar; AR, Mosassadeq; MD, Mohd Ashraf; Kamarulzaman, Mohd Nazli; Rahman, Mohd Nor Gohar; Z, Mahamood (Universiti Sains Malaysia, 2008)
To study the effects of intravesical eletrical stimulation of rabbit’s bladder and to apply the principle in human hypocontractile bladder as a method of bladderbiofeedback training.